Methods of the gas concentration sinusoidal and step changes generation for dynamic properties of gas concentration meters testing. (June 2016) - Kierat, Wojciech; Popiolek, Zbigniew
Highlights: Methods of testing of gas concentration meters dynamic properties are presented. Generators of step and sinusoidal changes in gas concentration are proposed. Results of step and sinusoidal dynamic properties tests showed a good agreement. Abstract: The generation methods of a gas concentration sinusoidal and step changes for dynamic properties assessment of the fast gas concentration meters are described. The need of such fast measurements occurs together with the rising scientists' interest in contaminants and microorganisms dispersion in the air, especially during the tests of the risk of infection. While the laboratory tests are performed, the tracer gas instead of a infected air is used. Due to the high selectivity, good long-term stability and a wide measurement range, the infrared absorption method for measuring the gas concentration is used. The dynamic properties of this method are limited by the need of the exchange of the gas sample in the measuring chamber. Both constructed generators allow to obtain gas concentration changes with specified amplitude and frequency. The results of step and sinusoidal tests of selected CO2 concentration meter were compared and they showed a good agreement.